Autoimmune Encephalitis With Psychotic Manifestations and Cognitive Impairment Presenting as Schizophrenia: Case Report and Literature Review - Luo, Yuanyuan; Li, Jieying; Jiang, Fugui; Tan, Arui; Qin, Xiaohong; Xiao, Xiaoqiang; Wang, Zuxing; Wang, Peijia; Yi, Yang; Li, Juan; Yuan, Shuai; Liu, Lei; et al. (Frontiers in Psychiatry, 2022)
Autoimmune encephalitis is characterized by mental and behavioral symptoms, seizures, and cognitive impairment. The presence of schizophrenia needs to be distinguished from that of autoimmune encephalitis. Herein, we describe the case of a woman who exhibited abnormal mental behavior and cognitive impairment. The patient had experienced similar symptoms more than 20 years previously and had been diagnosed with schizophrenia. The patient’s psychotic symptoms improved after treatment with antipsychotic drugs; however, cognitive impairment persisted. She was diagnosed with anti-N-methyl-D-aspartate (NMDA)-receptor concurrent with anti-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-receptor encephalitis. She showed improvement after treatment with steroids and intravenous immunoglobulins (IVIgs). Furthermore, we reviewed the literature and found that, including the present case, 10 patients have been diagnosed with anti-NMDA concurrent with anti-AMPA-receptor encephalitis. Three of these patients were men and seven were women, and their ages ranged from 21 to 71 years. Moreover, seven (70%) patients had a history of tumors. Symptoms of these patients included psychotic symptoms, varying degrees of consciousness disturbance, seizures, dyskinesia, dystonia, autonomic dysfunction, agitation, and verbal reduction. Brain magnetic resonance imaging findings showed scattered fluid-attenuated inversion recovery hyperintensity had increased in subcortical white matter and/or medial temporal lobe in seven (70%) patients. After combination treatment, including tumor removal and administration of steroids, IVIg, plasma exchange, or immunity inhibitors, the symptoms improved in part of the patients. It is necessary to exclude autoimmune encephalitis for patients with psychiatric manifestations and cognitive impairment. Timely combination therapy is important in anti-NMDA-receptor concurrent with anti-AMPA-receptor encephalitis.